Predicting exposure of wildlife in radionuclide contaminated wetland ecosystems. (January 2015) - Stark, K.; Andersson, P.; Beresford, N.A.; Yankovich, T.L.; Wood, M.D.; Johansen, M.P.; Vives i Batlle, J.; Twining, J.; Keum, D.-K.; Bollhöfer, A.; Doering, C.; Ryan, B.; et al.
Abstract: Many wetlands support high biodiversity and are protected sites, but some are contaminated with radionuclides from routine or accidental releases from nuclear facilities. This radiation exposure needs to be assessed to demonstrate radiological protection of the environment. Existing biota dose models cover generic terrestrial, freshwater, and marine ecosystems, not wetlands specifically. This paper, which was produced under IAEA's Environmental Modelling for Radiation Safety (EMRAS) II programme, describes an evaluation of how models can be applied to radionuclide contaminated wetlands. Participants used combinations of aquatic and terrestrial model parameters to assess exposure. Results show the importance of occupancy factor and food source (aquatic or terrestrial) included. The influence of soil saturation conditions on external dose rates is also apparent. In general, terrestrial parameters provided acceptable predictions for wetland organisms. However, occasionally predictions varied by three orders of magnitude between assessors. Possible further developments for biota dose models and research needs are identified. Highlights: Terrestrial parameters provided acceptable predictions for wetland species. Choice of reference organism and occupancy factor resulted in largest differences. Soil density and saturation should be considered when assessing doses in wetlands. Abstract : Terrestrial parameters provide acceptable predictions for wetland organisms.